Association of Cardiovascular Disease in Patients with Mycosis Fungoides and Sézary Syndrome Compared to a Matched Control Cohort - Courtney M. Johnson; Sai M. Talluru; Bianka Bubic; Michelle Colbert; Priyanka Kumar; Hua-ling Tsai; Ravi Varadhan; Sima Rozati (Elsevier, 2023)
Mycosis fungoides/Sézary syndrome (MF/SS) produces a low-grade chronic inflammatory state that may be associated with an increased risk of cardiovascular (CV) events, as seen in other chronic, systemic dermatologic diseases. To assess this association, a retrospective, cross-sectional study was designed in which 421 patients with a biopsy-proven diagnosis of MF/SS were compared with a control cohort of 4,210 age-, gender-, and race-matched patients randomly selected from the National Health and Nutritional Evaluation Survey database. The MF/SS cohort had a 14% prevalence of CV events, which was not statistically different from the control population's prevalence of 13%. In the MF/SS cohort, a multivariable logistic regression model showed that older patients (OR = 1.05 for each year of age, 95% confidence interval = 1.02-1.07) and those diagnosed with hypertension (OR = 3.40, 95% confidence interval = 1.71-6.75) had a higher risk of a CV event (P < 0.001). Risk factors such as gender, race, smoking, diabetes, and obesity were not significantly associated with CV events. Findings suggest that in the MF/SS population, advancing age and hypertension are risk factors for CV events, requiring clinical recognition and management. In addition, further research is needed to understand the complex interplay of how chronic inflammation in MF/SS impacts the immune development of CV disease.